Menumbuhkan Semangat Membaca Dengan Mengenalkan Huruf Alfabet pada Anak-Anak Panti Asuhan Stergein Haga - Claudia Lumban Gaol; Gusti Pirandy (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Many students lose motivation in learning. This can be caused by various things. This study aims to foster a passion for reading by introducing letters of the alphabet. The method used is FGD (Focus Group Discussion) by forming study groups. The problem that occurs here is that many chikdren still do not know the letters of alphabet. This has an impact on the ability of children who are still low. Obstacles in recognizing letters experienced by children cause difficulties in understanding lessons and laziness to do assignments given by teachers at school. Some children have memorized the letters of the alphabet but do not know how the shape of the alphabet is. If left unchecked, this will result in learning outcomes for students not being optimal and not asexpected. In addition, there will be difficulties at the next level of education. The aim of this program has also been achieved, as evidenced by the motivation that has fostered enthusiasm for learning to recognize letters even to explore new things that have never been thought of before.